Poly[tetrakis(dimethylformamide)tris(μ4-terephthalato)trimagnesium] - Vandavasi Koteswara Rao; Matthias Zeller; Sherri R. Lovelace-Cameron (Acta Crystallographica Section E, 2012)
The title framework compound, [Mg3(C8H4O4)3(C3H7NO)4]n or [Mg3(bdc)3(DMF)4]n, was obtained as a side product of the solvothermal reaction of magnesium nitrate, terephthalic acid (bdcH2), and 1,3-bis(4-pyridyl)propane in a 1:2:1 ratio in dimethylformamide (DMF). The asymmetric unit consists of three MgII cations, three terephthalate anions, and four coordinating DMF molecules. One of the four DMF molecules was refined as disordered over two mutually exclusive positions, with an occupancy rate for the major moiety of 0.923 (4). The three MgII cations possess distorted octahedral coordination geometries that form linear Mg trimers. Of the three MgII cations, the central MgII is octahedrally coordinated by six different carboxylate O atoms. The terminal MgII cations are bonded to four O atoms of three bdc linkers and to two O atoms of coordinating DMF molecules. The compound has a two-dimensional 36-network structure parallel to (001) that is formed by connection of the Mg trimers as distorted octahedral nodes to the bdc ligands as linkers.